PENGARUH BERBAGAI INTENSITAS CAHAYA TERHADAP PERTUMBUHAN SEMAI CEMPAKA (Michelia champaca L.) DI PERSEMAIAN - Susilawati Susilawati; Wardah Wardah; Irmasari Irmasari (ForestSains, 2019)
Champak (Michelia champaca L.) is a flowering plant in the Magnoliaceae family that requires light as an energy source for photosynthesis. Low light intensity will adversely affected the plant growth. The objective of this study was to determine the effect of various light intensity levels on the growth of champak’s seedlings. It was carried out for three months, February to April 2016, at the Permanent Nursery of BPDAS Palu-Poso, Universitas Tadulako. Randomized Block Design was employed as the method, consisting of five treatments namely: I1 = Light intensity of 10%, I2 = Light intensity of 30%, I3 = Light intensity of 50%, I4 = Light intensity of 70 %, I5 = Light intensity of 90%. Each treatment consisted of two groups, namely Group 1 (seedling with 3-4 leaves) and Group 2 (seedling with 5-6 leaves), which were replicated six times, so there was a total of 60 seedlings as the samples. The parameters were the height, diameter, number of leaves, and leaf area. The results of this study indicated that before the seedlings reached 3-months after weaning, diverse light intensity levels insignificantly affected the observed parameters. Subsequently, it demonstrated the highest level of diameter (1.90 mm), leaf number (3.8 leaves), leaf area (291.01cm2), height (3.83 cm) were obtained by I1, I2, I4, and I5, respectively.